Helicobacter hepaticus cytolethal distending toxin promotes intestinal carcinogenesis in 129Rag2‐deficient mice. (20th February 2017) - Ge, Zhongming; Feng, Yan; Ge, Lili; Parry, Nicola; Muthupalani, Sureshkumar; Fox, James G.
Summary: Multiple pathogenic Gram‐negative bacteria produce the cytolethal distending toxin (CDT) with activity of DNase I; CDT can induce DNA double‐strand breaks (DSBs), G2/M cell cycle arrest, and apoptosis in cultured mammalian cells. However, the link of CDT to in vivo tumorigenesis is not fully understood. In this study, 129/SvEv Rag2 −/− mice were gavaged with wild‐type Helicobacter hepatics 3B1(Hh) and its isogenic cdtB mutant HhcdtBm7, followed by infection for 10 and 20 weeks (WPI). HhCDT deficiency did not affect cecal colonization levels of HhcdtBm7, but attenuated severity of cecal pathology in HhcdtBm7‐infected mice. Of importance, preneoplasic dysplasia was progressed to cancer from 10 to 20 WPI in the Hh‐infected mice but not in the HhcdtBm7‐infected mice. In addition, the loss of HhCDT significantly dampened transcriptional upregulation of cecal Tnfα and Il‐6, but elevated Il‐10 mRNA levels when compared to Hh at 10 WPI. Furthermore, the presence of HhCDT increased numbers of lower bowel intestinal γH2AX‐positive epithelial cells (a marker of DSBs) at both 10 and 20 WPI and augmented phospho‐Stat3 foci + intestinal crypts (activation of Stat3) at 20 WPI. Our findings suggest that CDT promoted Hh carcinogenesis by enhancing DSBs and activation of the Tnfα/ Il‐6 ‐Stat3 signaling pathway.